Soil contamination with Geohelminths at aboriginal settlement in Sungai Tiang, Jerantut, Pahang / by Fatin Hazirah Ishak - Ishak, Fatin Hazirah (2016)
Contamination of soil with soil-transmitted helminth (STH) is a potential route of infection and contribute a risk to public especially young children that tend to spend more time playing outdoor activities. The present study was conducted to determine the prevalence of soil samples contaminated with eggs or larvae from the different site of areas favored by children to play. Soil samples were obtained from the house, school, field, open area and along the road at the aboriginal settlement to examine the presence of helminthes using the modified formalin-ether sedimentation technique. Overall of the thirty soil samples, 7 (23.3%) were found to be positive contaminated with three genera of helminthes, including filariform larvae (13.3%) the highest, followed by Toxocara spp. (6.67%) and Trichuris trichiura (3.33%). The rate of contamination was found to be highest in the area around the field (50%), school (33.3%), house and along the road with the same findings (16.7%). The prevalence of STH being isolated from soil samples also prone to be influenced by the difference in socioeconomic status of the aborigines, soil type, climate and season of the countries. The occurrence filariform larvae, Trichuris trichiura and Toxocara spp. from contaminated soil highlighted the need for the establishment of health programme regarding the importance of personal hygiene and preventive measures in reducing the risk of transmission to the community.